Analysis Model Social Emotional Learning (SEL) with Local Cultural Integration in Madrasah Ibtidaiyah - Chofifah, Chaesa Nur; Syafril, Syafrimen; Amriyah, Chairul (Journal of Basic Education Research, 2026)
Purpose of the study: Mto analyze the application of the social emotional learning (SEL) model, the integration of local cultural values in social emotional learning (SEL), and the competence of teachers in implementing social emotional learning (SEL) in Madrasah Ibtidaiyah. Methodology: This study uses the Systematic Literature Review (SLR) method, the literature used between 2021-2025 sourced from scientific databases in the form of Scopus, ERIC, DOAJ, and Google Scholar. This research utilizes the Publish or Perish 8 software. Main Findings: The study found that the integration of Social Emotional Learning (SEL) in Madrasah Ibtidaiyah becomes effective when local cultural values are internalized through collaborative, reflective, and contextual learning such as storytelling, traditional games, the use of regional languages, and mutual cooperation activities. This approach improves self-awareness, empathy, social skills, and responsible decision-making. The success of implementation is also influenced by teachers' competence in understanding SEL, building relationships, managing emotions, applying holistic pedagogy, and having cultural sensitivity so that SEL is integrated into school culture inclusively. Novelty/Originality of this study: The novelty of this study lies in the development of a learning model in Madrasah Ibtidaiyah that not only forms intellectual intelligence, but also balances the social-emotional and moral-spiritual aspects of students. This research is a guideline in designing learning based on the integration of local cultural values to foster empathy, social intelligence, and self-control.